Zmiany obyczajów motorem zmian językowych (nazwy zwyczajów) - Migdał, Jolanta; Piotrowska -Wojaczyk, Agnieszka (Slavia Occidentalis, 2015)
In this article, we take a closer look at the way in which names of habits operate in dictionaries and therefore in the Polish language. We refer our observations to an analysis of sixteen dictionary entries of our interest. What is more, we have confronted these entries with the results of questionnaires distributed among the students of the Poznań and Kalisz Institutes of Polish Philology. The analysed dictionary material provides an interesting insight and, more importantly, highlights the considerable discrepancy between dictionary theory and the practical command of the analysed words.